From hybrid TV towards transmedia: Recent marketing advances of the New Media developments - Wen-yi Hsu; Stone Shih (International Telecommunications Society (ITS), 2013)
Large broadcasters and independent media companies are already aware of the global developments in transmedia storytelling and understand that this is the trend (Gambarato, Renira R., 2012). In Taiwan, the HwaCom New Media project started with a government funded HbbTV development project, and then turned into a transmedia trial. The Fun Travel infrastructure has been built since June, 2013. The HwaCom Systems, Inc. establishes alliances to gain access to other firms' valuable resources. This study focuses on single case and tries to provide an exploration of how strategic alliances help the HwaCom New Media project achieve resource combinations through the resource-based theory of strategic alliances. To facilitate this study, direct observations and a focus group interview were conducted to explore some insights of this trial case...
Keywords: 330; complementary resources; Hybrid Broadcast Broadband Television (HBBTV); resource-based theory of strategic alliances; The HwaCom Systems; Inc.; transmedia storytelling (TS)